Capital Markets, Temporary Migration and Entrepreneurship: Evidence from Bangladesh - Laurent Bossavie; Joseph-Simon Goerlach; Caglar Ozden; He Wang (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2023)
This paper examines international temporary migration as an intermediary step among aspiring entrepreneurs to accumulate the needed capital when they face credit constraints at home. The analysis is based on a representative dataset of lifetime employment histories of return migrants from Bangladesh. After establishing the credit constraints that potential entrepreneurs face, the paper shows that non-agricultural self-employment rates are significantly higher among returning migrants over half versus around 20% of non-migrants. Most migrants transition into self-employment by using their savings from abroad as the main source of financing. The paper then offers, for the first time, a detailed account of the financial costs and benefits of international migration. Our findings suggest that temporary migration can contribute to the structural transformation of lower-income countries by enabling credit-constrained workers to enter into non-agricultural entrepreneurship.
Keywords: 330; Temporary migration; credit constraints; risky investment; entrepreneurship